Molecular characterization of dermal lymphatic endothelial cells from primary lymphedema skin. - Ogunbiyi, S; Chinien, G; Field, D; Humphries, J; Burand, K; Sawyer, B; Jeffrey, S; Mortimer, P; Clasper, S; Jackson, D; Smith, A (2011)
BACKGROUND: Lymphatic endothelial cells from primary lymphedema skin have never been cultured nor characterized. A subgroup of patients with primary lymphedema undergo surgery to bring about an improvement in their quality of life. The aim of this study was to culture and characterize LECs from the skin of these patients. METHODS AND RESULTS: Lymphatic endothelial cells were isolated and cultured from the skin of patients with primary lymphedema and from normal skin. The isolated cells were compared in their ability to form microvascular networks in a three-dimensional culture medium, and in their response to treatment with vascular endothelial growth factors A, C, and D. Whole tissue transcriptional profiling was carried out on two pools of isolated lymphatic endothelial cells--one from primary lymphedema skin and the other from normal skin. Lymphatic endothelial cells from primary lymphedema skin form tubule-like structures when cultured in three-dimensional media. They respond in a similar fashion to stimulation with the vascular endothelial growth factors A, C, and D. Comparative analysis between lymphedema tissue and normal tissue (fold change >2) showed differential expression of 2793 genes (5% of all transcripts), 2184 upregulated, and 609 downregulated. Genes involved in cellular apoptosis (vascular endothelial growth inhibitor, zinc finger protein), extracellular matrix turnover (matrix metalloproteinase inhibitor-16), and type IV collagen deposition were upregulated. Various pro-inflammatory genes (interleukin-6, interleukin-8, interleukin-32, E-selectin) were downregulated. CONCLUSION: Cellular adhesion, apoptosis, and increased extracellular matrix turnover play a more prominent role in primary lymphedema than previously thought. In addition, the acute inflammatory response is attenuated as evidenced by the downregulation of various pro-inflammatory genes.This sheds further light on the interplay of the various pathological processes taking place in primary lymphedema.